2001
DOI: 10.1002/1097-4636(2001)58:1<61::aid-jbm90>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Loading improves anchorage of hydroxyapatite implants more than titanium implants

Abstract: Roentgen Stereophotogrammetric Analysis (RSA) studies have shown that the quality of the early fixation of implants has a dominant effect on their long-term function. To evaluate methods to improve their fixation, we examined the influence of mechanical loading and surface coating on the quality of the bone-implant interface. We compared the fixation of a cylindrical, stable 6.0 mm implant initially surrounded by a 0.75 mm concentric gap, after 4 weeks of loaded or unloaded conditions. Two types of surfaces we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0
2

Year Published

2004
2004
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 31 publications
3
34
0
2
Order By: Relevance
“…Hydroxyapatite revealed greater bone contact than titanium. Bone contact was further increased under loaded conditions only for hydroxyapatite implants, while loading increased fibrous tissue coverage for titanium implants [32]. Similar results were found in the present study: The two implant surfaces revealed a different response to load.…”
Section: Article In Presssupporting
confidence: 90%
See 1 more Smart Citation
“…Hydroxyapatite revealed greater bone contact than titanium. Bone contact was further increased under loaded conditions only for hydroxyapatite implants, while loading increased fibrous tissue coverage for titanium implants [32]. Similar results were found in the present study: The two implant surfaces revealed a different response to load.…”
Section: Article In Presssupporting
confidence: 90%
“…A reason for the controversial results of coated Al 2 O 3 in the both implant models, however, could be the different mechanical conditions at the implantation sites. Mouzin et al [32] reported that loading improves anchorage of hydroxyapatite implants more than titanium implants. The authors compared stable but mechanically loaded and unloaded implants.…”
Section: Article In Pressmentioning
confidence: 99%
“…Following intravenous administration of alendronate (miniosmotic pump; 0.01 mg/kg/day), bone volume was similar to counterparts not exposed to particles. While these results are encouraging, it should be noted that the experimental protocols did not allow mechanical stability or weight bearing to be controlled (Mouzin 2001).…”
Section: Discussionmentioning
confidence: 89%
“…Perizzolo et al [33] reported on an in vitro study in which a synergistic effect was observed between topography (micromachined grooved surfaces) and chemistry (Ca-P coatings) for the initiation of bonelike nodule formation. Soballe et al reported on the benefits of an HA coating over a Ti plasma-sprayed layer that results in a very irregular surface topography [34]. The application of plasma-sprayed 'HA' (actually a mixture of different Ca-P phases) over sintered porouscoated implants (sintered Ti fibres) was reported by Rivero et al [25] to give faster bone ingrowth.…”
Section: Discussionmentioning
confidence: 99%